Intellectuals and the Communist idea : the search for a new way in Czech lands from 1890 to 1938 - Cabada, Ladislav (Lexington Books, 2010)
Intellectuals and the Communist Idea describes how the Communist ideology penetrated into Czech culture and politics from the dawn of the twentieth century into the late 1930s, just before the outbreak of WW II in Europe. Based mainly upon the research of contemporary primary sources, the analysis examines the complex issue of personal reasons and individual motivations, appealing slogans, and ideological and power peripheries connected with the formation of the relationship between the newly-founded Communist Party in Czechoslovakia and the left-wing artists and intellectuals declaring themse.